ANALISIS PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) TERHADAP KETERAMPILAN SOSIAL PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR : ANALISIS PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) TERHADAP KETERAMPILAN SOSIAL PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Wulandari, Fauziyyah Kania; Ahmad Mulyadiprana2 (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the impact of implementing the Teams Games Tournament (TGT) model on the improvement of social skills in Pancasila Education learning at the elementary school level. The approach used is a literature review by collecting and analyzing various sources such as scientific articles, journals, and other documents relevant to the topic. Based on the analysis of 10 journal articles, the results indicate that the TGT model is effective in developing students' social skills. Social skills play a crucial role in shaping children's social interactions, and the TGT model presents a promising approach to improving these abilities. The implementation of this model can help students become more proficient in socializing, collaborating, communicating, and enhancing their interpersonal intelligence.